Practice on mobile phone etiquette among UiTM Shah Alam students / Nor Fadzilah Isa - Isa, Nor Fadzilah (2006)
Mobile phones are a pervasive new communication technology and had become the most common information access devices with almost of the global population are using it. However the many benefits that mobile phones provide are at times overshadowed by the problems they create, as when one person's mobile phone disrupts a group activity, such as class or meeting. Mobile phone distraction could be overcome with the practicing of mobile phone etiquette. Mobile phone etiquette involves following some simple guidelines of common courtesy when using mobile phone in public, designed is to make public places more enjoyable for all. The distraction of mobile phone usage could happen anywhere where it involves people around us. As much we know that most of the higher learning institutions' students own their mobile phone, the mobile phone distraction also applies in this environment. Most of these students know about the mobile phone etiquette but they do not practice the etiquette. This study seeks to determine whether the students willing to practice mobile phone etiquette and also identify their level of awareness on mobile phone etiquette. Besides, the study also identifies the behavior of mobile phone usage among the students. To determine the willingness to practice mobile phone etiquette, an extended model based upon the Theory of Planned Behavior (TPB) is used. Primary data were collected through questionnaires. Correlation coefficient analyses result shows that the respondents are willingly to practice the mobile phone etiquette but one of the determinants in the TPB does not influence the willingness to practice this etiquette.